Answer:
6 students
Step-by-step explanation:
6 times 1.5 equals 9
Answer:
Your answer is
Fourth grade student = 25%
Fifth grade= 33.33%
Sixth grade= 41.67%
Want more answer then follow me, like and MARK MY ANSWER AS BRAINLIST ANSWER.
I need that urgently.
Answer:
Lin's mother is the type that finds information about the area
Three because the smaller the a value is, the narrower the graph.
Answer:
![(x+2)(x-2)(x+1)(x-1)](https://tex.z-dn.net/?f=%28x%2B2%29%28x-2%29%28x%2B1%29%28x-1%29)
Step-by-step explanation:
We want to factor the expression
.
First, notice that this is in quadratic form. In other words, both the exponents have even power.
Therefore, we can make a substitution to simplify the expression.
So, let’s let
.
Our expression is the same as:
![(x^2)^2-5(x^2)+4](https://tex.z-dn.net/?f=%28x%5E2%29%5E2-5%28x%5E2%29%2B4)
Substitute:
![u^2-5u+4](https://tex.z-dn.net/?f=u%5E2-5u%2B4)
Now, we can factor like normal. We can use -1 and -4. Therefore:
![=(u-4)(u-1)](https://tex.z-dn.net/?f=%3D%28u-4%29%28u-1%29)
We can now substitute back u:
![=(x^2-4)(x^2-1)](https://tex.z-dn.net/?f=%3D%28x%5E2-4%29%28x%5E2-1%29)
Both of these can be factored furthered using the difference of two squares:
![(a^2-b^2)=(a+b)(a-b)](https://tex.z-dn.net/?f=%28a%5E2-b%5E2%29%3D%28a%2Bb%29%28a-b%29)
Therefore, we will have:
![=(x+2)(x-2)(x+1)(x-1)](https://tex.z-dn.net/?f=%3D%28x%2B2%29%28x-2%29%28x%2B1%29%28x-1%29)
And we are done!